Takip silip a qualitative study on the utilization of the hidden camera as an investigative tool - Cinco, Ariane Corinne Advincula
"Takip Silip is a study that tried to understand the hidden camera as a tool for investigative reporting within the context of the law. The objective of this study is to determine the significance of the hidden camera to the investigative program, Imbestigador. Furthermore, this study aims to ascertain the provisions in the Constitution that would serve as guidelines in the employment of the hidden camera as a tool for investigative reporting. In addition to that, this study also tried to discover the extent of the device's usefulness to the investigative program Imbestigador. To measure the factors mentioned above, the researcher made use of two qualitative methods of research; interview and content analysis. The researcher interviewed two authorities on the law in order to understand the provisions of the law that define how the hidden camera could be used efficiently as a research tool. One of the interviewees is Judge Norma Cinco, presiding Judge of the Minicipal Trial Court of Capoocan in Leyta. The other interviewee is Attorney Antonio Arellano. Atty. Arellano is a prominent lawyer, as well as a media personality. He hosts Ito ang Batas with Attorney AGA, a public service program in DZXL. He also writes occassional columns for Pilipino Star Ngayon. The researcher also interviewed two staffers from Imbestigador in order to get an insider's view of the program. The researcher interviewed Mr. Junie Castillo, Executive Producer of Imbestigador and Ms. Vanessa Ulgado, Researcher for Imbestigador. In addition to the interviews, the researcher also reviewed 12 episodes of Imbestigador to ascertain the situations in which the hidden camera is used and to measure the program's degree of dependence to the device. The interviews with the authorities on the law yielded insights regarding the legal and ethical use of the hidden camera. Because of the presence of Anti-Wiretapping Law or RA 4200, investigative reporters who obtain secretly, or through the hidden camera, may use the video part but not the audio element that accompanies the visuals. RA 4200 prohibits the secret taping of private communication. Atty. Arellano contested, however, that the Imbestigador's use of the hidden camera is legal on the ground that Imbestigador is a private entity. As such, the program may use the hidden camera to detect and strengthen evidence against alleged violators of the law. In the interview with the staffers from Imbestigador, the researcher found out that the main reason for the hidden camera's inclusion into the program is the device's capability to inject an element of excitement to the realm of investigative reporting. The hidden camera is also significant to the program in the sense that the device enables the program to deliver on its promise to protect and serve the public interest by coming up with in=depth, well-researched reports. The staffers contended that the hidden camera makes the exploration of a story more comprehensive and more thorough. The hidden camera is effective in ferreting out information that the subject would otherwise conceal if he or she knows that he or she is being taped. The hidden camera is also useful in proving the guilt of alleged violators of the law. The hidden camera is used in stories which concern government officials and government transactions, in open areas, and in stories which concern matters of public interest. It was observed that the hidden camera is commonly used to document entrapment operations and confrontation scenes. Except in special features, the hidden camera is never used as primary tool for investigation. The device is always used to obtain information that would supplement the data gathered through interviews."